2017
DOI: 10.1080/10409238.2017.1373741
|View full text |Cite
|
Sign up to set email alerts
|

New tricks for the glycyl radical enzyme family

Abstract: Glycyl radical enzymes (GREs) are important biological catalysts in both strict and facultative anaerobes, playing key roles both in the human microbiota and in the environment. GREs contain a backbone glycyl radical that is post-translationally installed, enabling radical-based mechanisms. GREs function in several metabolic pathways including mixed acid fermentation, ribonucleotide reduction, and the anaerobic breakdown of the nutrient choline and the pollutant toluene. By generating a substrate-based radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(137 citation statements)
references
References 126 publications
(230 reference statements)
3
129
0
Order By: Relevance
“…In terms of gene network interactions and function of the rumen microbiome, we found that Glycyl Radical and Peptidase function, were positively correlated to each other. The Ruminococcaceae family undergo changes with the inclusion of NA and had a positivel correlation with the abundance of protein Glycyl Radical genes, which are found to contribute to environmental resilience, and are also potentially related with VFA production [42]. The abundance of Prevotellaceae was negatively correlated with Ruminococcaceae; the two major bacterial families found in our study.…”
Section: Discussionsupporting
confidence: 46%
“…In terms of gene network interactions and function of the rumen microbiome, we found that Glycyl Radical and Peptidase function, were positively correlated to each other. The Ruminococcaceae family undergo changes with the inclusion of NA and had a positivel correlation with the abundance of protein Glycyl Radical genes, which are found to contribute to environmental resilience, and are also potentially related with VFA production [42]. The abundance of Prevotellaceae was negatively correlated with Ruminococcaceae; the two major bacterial families found in our study.…”
Section: Discussionsupporting
confidence: 46%
“…is an abundant glycyl radical enzyme (GRE) 139,140 that catalyzes degradation of choline to trimethylamine (TMA) and acetaldehyde in the human gut microbiome (Scheme 2). After formation of a stable α-carbon glycyl radical at G821 by an activating enzyme, CutD, 74 the formation of a short-lived and reactive cysteine radical, C489, has been proposed 73,74 that can then initiate choline decomposition via C-H abstraction.…”
Section: Cutc (Ref 138)mentioning
confidence: 99%
“…CutC (ref. 138) is an abundant glycyl radical enzyme (GRE) 139,140 that catalyzes degradation of choline to trimethylamine (TMA) and acetaldehyde in the human gut microbiome (Scheme 2). After formation of a stable α-carbon glycyl radical at G821 by an activating enzyme, CutD, 74 the formation of a short-lived and reactive cysteine radical, C489, has been proposed 73,74 that can then initiate choline decomposition via C-H abstraction.…”
Section: View Article Onlinementioning
confidence: 99%